The Effect of Tax Socialization, Tax Understanding, and Tax Service Quality on Individual Taxpayer Compliance - Rifkhan; Akbar, Achmad Sutani (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
Taxpayer compliance remains a critical challenge for Indonesia's state revenue collection, as approximately 70% of the national budget (APBN) depends on tax revenues, yet non-compliance persists among individual taxpayers due to limited knowledge and service gaps. This study aims to analyze and provide empirical evidence of the effect of tax socialization, tax understanding, and tax service quality on individual taxpayer compliance, both partially and simultaneously. The study employs a quantitative approach with a causal-associative design. The population consists of 638,364 individual taxpayers registered at KPP Pratama Ciawi, Bogor. Using the Slovin formula with a 10% margin of error, a sample of 100 respondents was obtained through purposive sampling. Data were collected through a structured questionnaire measured on a Likert scale and analyzed using multiple linear regression preceded by validity, reliability, and classical assumption tests. The results show that tax socialization has no significant effect on taxpayer compliance, whereas tax understanding and tax service quality have significant positive effects; simultaneously, all three independent variables significantly influence taxpayer compliance, with an R2 contribution of 49%. The novelty of this study lies in the integrated examination of the three tax-authority-driven determinants within the local context of KPP Pratama Ciawi, offering evidence that socialization alone, without adequate understanding and service quality, is insufficient to drive compliance. The findings imply that the Directorate General of Taxes needs to redesign socialization strategies to be more comprehensible, deepen taxpayer education, and continuously improve service quality to strengthen voluntary compliance.